2020
DOI: 10.1101/2020.06.03.20121814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disparities in COVID-19 related knowledge, attitudes, beliefs and behaviours by health literacy

Abstract: Objectives: To explore the variation in understanding, attitudes and uptake of COVID-19 health advice during the 2020 pandemic lockdown by health literacy. Study design: National cross sectional community survey. Setting: Australian general public. Participants: Adults aged over 18 years (n=4362). Main outcome measures: Knowledge, attitudes and behaviours related to COVID-19; health literacy and socio-demographic factors. Results: People with inadequate health literacy had poorer understanding of COVID-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 16 publications
3
46
0
1
Order By: Relevance
“…This finding is in line with the results of studies carried out in other countries. According to McCaffery et al, using the STAI questionnaire on a sample of adult Australians, an inadequate level of HL was associated with a lower perceived seriousness of threat, but a higher level of anxiety [90]. Wolf et al also found a greater degree of anxiety in patients living in the USA suffering from chronic diseases who also had low HL [48].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the results of studies carried out in other countries. According to McCaffery et al, using the STAI questionnaire on a sample of adult Australians, an inadequate level of HL was associated with a lower perceived seriousness of threat, but a higher level of anxiety [90]. Wolf et al also found a greater degree of anxiety in patients living in the USA suffering from chronic diseases who also had low HL [48].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline data were collected from all states/territories in April 2020 during COVID-19 lockdown, with a subsample followed-up in June 2020 when restrictions eased. Of 4362 baseline participants, those reporting high blood pressure with no other chronic conditions (n=466) were randomly matched to individual healthy controls based on age (+/-3 years), gender, education and health literacy adequacy (given baseline survey differences(McCaffery et al, 2020)). The initial match rate was 95.7%, with constraints relaxed until all cases were paired.…”
Section: Methodsmentioning
confidence: 99%
“…Public health messaging not only should ensure translation of messages but also understand the cultural differences that may interfere with practicing preventive behaviours. Unlike other Australian surveys [5,8], our survey looked beyond quantifying knowledge and attitudes to include qualitative content analyses to identify specific reasons for participants' misconceptions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Misinformation about prevention, transmission, and treatment of COVID-19 has the potential to derail these efforts. International and Australian-focused online surveys suggest 71% -93% of participants [5,6] could identify preventive behaviours (e.g., hand hygiene, physical distancing), but the proportion of individuals who self-report practicing these behaviours were fewer, ranging from a low of 45% in a survey of UK participants [7] to 85% in an Australian sample [8]. The difference between the high proportion of people knowing appropriate prevention behaviours and the lower proportion of those reporting to practice the behaviour, suggests that knowledge alone is insufficient to change behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation